2018
DOI: 10.1002/jmri.26269
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intra‐ and Interscanner Reliability of MRI Protocols for Spinal Cord Gray Matter and Total Cross‐Sectional Area Measurements

Abstract: 1 Technical Efficacy: Stage 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 33 publications
2
25
1
Order By: Relevance
“…This is in line with an average area of about 80 mm 2 as detected in the previous study for CSA in the 20‐25 years range 10 . Although different acquisition protocols were used in the two studies, we previously showed that, using Jim, they provide comparable CSA estimates 8 …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This is in line with an average area of about 80 mm 2 as detected in the previous study for CSA in the 20‐25 years range 10 . Although different acquisition protocols were used in the two studies, we previously showed that, using Jim, they provide comparable CSA estimates 8 …”
Section: Resultssupporting
confidence: 90%
“…Recent advancements in magnetic resonance imaging (MRI) technology have allowed for the acquisition of high‐resolution SC magnetic resonance (MR) images at cervical and thoracic levels. In particular, T2*‐weighted and phase sensitive inversion recovery (PSIR) sequences have been developed and used to quantitatively assess GM/WM damage in neurodegenerative diseases of the CNS 7,8 . In the absence of cutting‐edge SC dedicated acquisitions, SC atrophy at the upper cervical levels (defined in terms of cross‐sectional area [CSA]) can be assessed using routinely acquired T 1 ‐weighted brain scans that include the upper cervical cord 9 …”
Section: Introductionmentioning
confidence: 99%
“…Compared to former analyses of reliability of other automated spinal cord segmentation tools, the ICC of spinal cord CSA at C6/C7 is currently lower than previously reported (e.g. ( Papinutto and Henry, 2019 , De Leener et al, 2015 ). As the ICC improved tremendously after exclusion of one outlier, we suspect the low inter-rater agreement to be caused by the manual labeling process.…”
Section: Discussioncontrasting
confidence: 60%
“…Currently, there are some pipelines available for SC segmentation, 18,19 but we chose the SCT because it is highly reproducible and less affected by artifacts. [12][13][14] Then, we were able to show, for the first time, that cervical SC atrophy is found in some but not all HSP subtypes. Moreover, SC morphometric changes in HSP-SPG4 and SPG11 extend to both GM and WM.…”
Section: Discussionmentioning
confidence: 72%
“…13 This pipeline has high segmentation accuracy and acceptable intra-and interscanner reliability. 13,14 The measurement of these segmented structures can contribute to identifying potential biomarkers for HSPs through understanding the pattern of SC damage. This might be helpful for diagnostic purposes and also to assess disease progression.…”
mentioning
confidence: 99%